An Indole-Rich Postbiotic Reduces Itching in Dogs: A Randomized, Double-Blinded Placebo-Controlled Study - Aylesse Sordillo; Jonna Heldrich; Raphaël Turcotte; Ravi U. Sheth (Animals, 2025)
Many dogs suffer from pruritus, which is commonly caused by atopic dermatitis and associated with skin inflammation. The immune system and inflammatory response, and in particular the gut–skin axis, are central to the pathogenesis of atopic dermatitis. Managing atopic dermatitis involves complex, iterative treatment plans; early strategies supporting gut–skin health are needed to prevent elevated itching from progressing toward a disease condition requiring drug therapy. This double-blind, placebo-controlled, randomized trial evaluated the ability of a novel, indole-rich canine immune health postbiotic (CIHP) to reduce itching and promote a healthy gut microbiome in dogs with subclinical, but elevated itching behavior. Thirty dogs were stratified into two groups based on baseline scratching frequency, receiving either CIHP or placebo as a powder topper for 28 days. Canine itching was evaluated through accelerometer-based tracking and the Pruritus Visual Analog Scale (PVAS) score on Days 0, 7, 14, 21, and 28. Skin and coat health was assessed on Days 0, 14, and 28, and the gut microbiome was sequenced from fecal samples on Days 0 and 28. CIHP reduced scratching by 20% relative to the baseline (p = 0.032) and PVAS score by 27% compared to the placebo (p = 0.02). CIHP improved skin and coat quality compared to the placebo at Day 14 (p = 0.01) and increased Shannon diversity by 4.6% (p = 0.043), shifting gut microbiome composition. These findings validate this postbiotic’s ability to reduce itching in dogs with subclinical, but elevated itching behavior, provide evidence of promoting a healthy gut–skin axis, and suggest potential as an early intervention in the context of pruritic conditions, as well as for broader immune-related benefits.